Sensorless Speed Control of Independent Dual-PMSM Drives Fed by a Five-Leg Inverter - Mat lazi, Jurifa; Ibrahim, Zulkifilie; Yusoff, Marianna; Mat Isa, Siti Noormiza; Mohd Yaacop, Nurazlin; Abu Hasim, Ahmad Shukri (2012)
Various control algorithms have been investigated for speed sensorless of an AC motors using three-leg inverter by other researchers. Unfortunately, these sensorless techniques are mainly focus on single motor controlled drive with a single three-le inverter. Resent research has shown that the dual-motor drives can be independently controlled by using a Five-Leg Inverter (FLI). This paper introduces the new control strategy based on speed sensorless technique of independent dual- Permanent Magnet Synchronous Motor (PMSM) drives using FLI. The simulation is implemented in MATLAB/Simulink to evaluate the overall motor drive performance. The transient behavior is examined for various speed commands, load disturbance, inertia and during zero speed operation, so that a thorough comparison is enable. The simulation results also proved that the performance characteristics of sensorless dual-PMSM are almost similar to the sensory system except for the startup condition. For future research, there is a need to emphasize on the start-up method for sensorless dual-PMSM drives.